CULTURAL HERITAGE AT RISK IN SICILY: MILITARY INTERFERENCE AT THE CASTLE OF BRUCOLI (SYRACUSE, 1941-42) - Antonino Crisà, (PEOPLE: International Journal of Social Sciences, 2025)
Within the vast European context, Italy was strongly affected by World War 2 from June 1940. Particularly, Sicily, a Mediterranean island rich heritage remains, became a major target for enemy aircraft bombing due to its proximity to the African frontline, especially right before the Allied landing (July 1943). In such an emergency context, Italian authorities actualized a series of measures to protect monuments (e.g. installing protective scaffoldings and sandbags). However, protecting cultural heritage often clashed with the military necessity of defending Sicily from any potential enemy attack. What do we know about peculiar quarrels between military and safeguarding national authorities in case a monument was supposed to be safeguarded? Benefitting from a series of archival records which are still fully neglected by scholars, the main aim of my paper is to evaluate a vital case study on the protection of the medieval Castle of Brucoli, a small coastal historical centre, 35 km north from Syracuse. Between 1941 and 1942, a battalion of the Italian army stationed in Sicily began to utilize the castle for military purposes to store straw and firewood. The Superintendent of Monuments in Catania protested vehemently for such a decision asking the intervention of Giuseppe Bottai, Fascist Minister of Education. My paper is strictly connected to a major research project carried out at Ghent University (2020-22) whose results are now forthcoming as a monograph. First, I outline the history of heritage protection in Sicily in the early 1940s contextualizing the event of the Castle of Brucoli in the wider European framework. Then, I assess the episode highlighting the historical relevance of data through records. My analysis will lead towards vital outcomes including a remarkable reconstruction of social, military and civilian networks involved in the protection/use of monuments in war context complementing results of the above-mentioned project profitably.